Prospective applications of phenolic compounds in processing by-products of date fruits (Phoenix dactylifera L.) - Nagwa K.-E. M. Salih; Muneeba Zubair Alam; Sabeera Haris; Afaf Kamal-Eldin; Ali H. Al-Marzouqi (Discover Food)
Abstract This review highlights the potential of generating value-added products rich in phenolic compounds from date fruit (Phoenix dactylifera L.) and its processing by-products. The review presents the phenolic contents in date fruits and seeds and their potential applications as feedstocks in food, pharmaceutical, and cosmetic industries. It discusses the extraction and characterization protocols for phenolic compounds and the research that is needed to fill the gaps in knowledge and standardization methods. The safety and suitability of date seeds as a functional food ingredient were discussed. The review aimed to serve as a guide towards innovative, scalable, and sustainable strategies for maximizing the environmental and economic benefits of date fruits. Graphical Abstract